1984
DOI: 10.1121/1.391605
|View full text |Cite
|
Sign up to set email alerts
|

Performance on frequency-discrimination tasks by musicians and nonmusicians

Abstract: Auditory discrimination abilities of professional musicians were compared with those of nonmusicians. The stimuli for the frequency-discrimination tasks were 300-msec sinusoidal tones, 300-msec square waves, and tone patterns consisting of ten 40-msec tones played sequentially. The musicians’ difference thresholds for single tones were between Δf /f=0.001 and 0.0045. One-half of the nonmusicians attained thresholds almost as low; the rest attained larger thresholds, up to Δf /f=0.017. The results for the patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
126
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(161 citation statements)
references
References 0 publications
33
126
2
Order By: Relevance
“…Relatedly, electro and magnetoencephalography (EEG & MEG) data indicate enhanced cortical responses in musicians to the timbre of the specific instrument they perform (versus an instrument they do not), both in adults (Pantev et al, 2001;Shahin et al, 2003) and children (Shahin et al 2004;Trainor et al, 2003). Moreover, string and woodwind players -who constantly monitor and adjust the pitch they are producing -can discriminate frequency differences more finely than musicians who play fixed pitch instruments like piano (Micheyl et al, 2006;Spiegel & Watson, 1984).…”
Section: Musicianship and Auditory Perceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relatedly, electro and magnetoencephalography (EEG & MEG) data indicate enhanced cortical responses in musicians to the timbre of the specific instrument they perform (versus an instrument they do not), both in adults (Pantev et al, 2001;Shahin et al, 2003) and children (Shahin et al 2004;Trainor et al, 2003). Moreover, string and woodwind players -who constantly monitor and adjust the pitch they are producing -can discriminate frequency differences more finely than musicians who play fixed pitch instruments like piano (Micheyl et al, 2006;Spiegel & Watson, 1984).…”
Section: Musicianship and Auditory Perceptionmentioning
confidence: 99%
“…A considerable body of research suggests that musicians tend to out-perform non-musicians in perceiving fine differences in a number of basic auditory properties, including frequency and/or pitch (Spiegel & Watson, 1984;Micheyl et al, 2006; Kishon-Rabin et al, 2001;Amir, Amir & Kishon-Rabin, 2003;Nikjeh, Lister & Frisch, 2009; Koelsch, Schröger & Tervaniemi, 1999; GENERALITY AND SPECIFICITY IN MUSICAL EXPERTISE EFFECTS 6 Parbery-Clark et al, 2009b), tone interval size (Zarate, Ritson & Poeppel, 2012Siegel & Siegel, 1977), temporal interval size (Rammsayer & Altenmüller, 2006;Cicchini et al, 2012; Ehrle & Samson, 2005), and timbre (Pitt, 1994). Below, we review evidence for lower-level and contextually-relevant perceptual advantages in differently trained musician cohorts.…”
Section: Musicianship and Auditory Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, superior performance of B large subjects over the sighted reference group (R B, large ) and both groups of visually impaired subjects (VI no and VI small ) was confirmed in our pitchtimbre categorization experiment for the two most difficult conditions. Such performance of B large group was expected on the basis of earlier reports (Bogusz et al, 2012a;Wan et al, 2010;Gougoux et al, 2004;Tervaniemi et al, 2005;Spiegel, Watson, 1984).…”
Section: Pitch-timbre Categorization Experimentsmentioning
confidence: 72%
“…As some of blind and visually impaired people are musically or auditory trained, it may be interesting to determine the effect of their musical experience on the ability to solve basic psychoacoustic tasks. A number of studies have shown that sighted musicians perform better than sighted non-musicians in tasks related to pitch discrimination (Tervaniemi et al, 2005;Spiegel, Watson, 1984) and that classical musical training can lead to optimal or nearly optimal pitch discrimination performance (Micheyl et al, 2006;Kishon-Rabin et al, 2001). A possible reason for such performance is that the pitch is a fundamental dimension of auditory perception, which plays a basic role in music, for example: pitch variations over time are used to convey melodies.…”
Section: Introductionmentioning
confidence: 99%